2021
DOI: 10.1155/2021/8670474
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Continuous Subcutaneous Injection of Insulin Analogues in Pregnant Women with Diabetes Mellitus Complicated with Ketoacidosis

Abstract: Objective. To investigate the clinical effect of continuous subcutaneous injection of insulin analogues in pregnant women with diabetes mellitus complicated with ketoacidosis. Methods. A total of 92 pregnant patients with diabetes mellitus complicated with ketoacidosis from June 2014 to January 2021 were selected. All patients were randomly divided into an observation group and control group according to the method of random number. The control group received intravenous infusion of insulin, and the observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%